The Reality of Economic Growth towards Green Environment: A Study of Selected OECD Countries 1990-2010 - Gupta, Shilpi (International Journal of Environment, 2014)
Economic growth and green environment has a direct relation with health, habitat and well being of our society which depends largely on the natural environment. But on the other side the society is neglecting and often ignoring the benefits that nature provides for economic prosperity. This paper studies the role of environment in economic growth, the role of environmental policy in achieving improved environmental results, closely examine the evidence of decoupling production from environmental damages and discuss decoupling in the context of global economy. In order to study these aspects, we explored our comparative research with special reference to selected eight OECD nations namely-France, Germany, Ireland, Japan, Portugal, Turkey, UK and USA with coverage period of 1990-2010. The selection of the countries is based on their prominence in industrialised world and their close economic bounding with each other over a considerable period. The coverage period in the study is 20 years because some of the emission data are available till 2013 and some only up to 2010. In order to do a comparative research on various dimensions we take in to our study period between1990-2010. DOI: http://dx.doi.org/10.3126/ije.v3i3.11065 International Journal of Environment Vol.3(3) 2014: 78-88